PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN MASKAPAI GARUDA INDONESIA DI DENPASAR - Dewiwati Sujadi; Putu Nanda Paramesti Dewi (Journal Research of Management, 2022)
The world of industrial business is now increasingly widespread, one of which is the aviation industry. The aviation industry is one of the means of transportation that can make it easier for us to travel long distances but with a faster time. To analyze the effect of tangibles/physical evidence on customer satisfaction using Garuda Indonesia airline in Denpasar. This study aims to analyze the effect of reliability/reliability variable, responsiveness/responsiveness variable, assurance/guarantee, empathy/caring, on customer satisfaction in using Garuda Indonesia airline in Denpasar. This research uses a quantitative approach. Respondents in this study were customers who visited the Garuda Indonesia office in Denpasar, with a total sample of 95 respondents. The analysis technique used is multiple linear regression analysis. Physical evidence has a positive and significant effect on customer satisfaction in using the Garuda Indonesia airline in Denpasar. Reliability has a positive and significant effect on customer satisfaction in using the Garuda Indonesia airline in Denpasar. Responsiveness has a positive and significant effect on customer satisfaction in using the Garuda Indonesia airline in Denpasar. The guarantee has a positive and significant effect on customer satisfaction in using the Garuda Indonesia airline in Denpasar. Concern has a positive and significant effect on customer satisfaction in using Garuda Indonesia airline in Denpasar. Physical evidence has a beta value of 0.224. Reliability has a beta value of 0.128. Responsiveness has a beta value of 0.248. The guarantee has a beta value of 0.177. Concern has a beta value of 0.248. Beta Concern and Responsiveness have the same beta value, but seen from the tcount value of the concern variable has a higher value, this means that caring has a dominant influence on increasing or decreasing customer satisfaction in using Garuda Indonesia airline in Denpasar.